Benefit of transaminase elevations in establishing functional cure of HBV infection during nap‐based combination therapy. Issue 5 (26th February 2021) - Bazinet, Michel; Pântea, Victor; Placinta, Gheorghe; Moscalu, Iurie; Cebotarescu, Valentin; Cojuhari, Lilia; Jimbei, Pavlina; Iarovoi, Liviu; Smesnoi, Valentina; Musteata, Tatiana; Jucov, Alina; Dittmer, Ulf; et al.
Abstract: Treatment of HBV infection with nucleic acid polymers and pegIFN is accompanied by transaminase elevations in 95% of participants. HBV viral rebound, partial cure (HBV DNA < 2000 IU/mL, normal ALT) or functional cure (HBV DNA target not detected, HBsAg <LLOQ, normal ALT) occurred in 27%, 38% and 35% of participants. Correlations between ALT, AST and GGT elevations, virologic baseline, response during therapy and HBV therapeutic outcome were investigated. A retrospective analysis of all 40 participants in the REP 401 study (NCT02565719) included maxima and area under the curve for ALT, AST and GGT, baseline virology, HBsAg and anti‐HBs response and HBV therapeutic outcomes. ALT, AST and GGT elevations were asymptomatic, independent of baseline virologic status and anti‐HBs response but correlated with HBsAg reduction ≥3 log10 from baseline. Functional cure was associated with significantly lower HBsAg during the nadir of ALT flares versus viral rebound or partial cure. ALT elevations >3X ULN while HBsAg was <1 IU/mL occurred in 3/11 (27%), 11/15 (74%) and 14/14 (100%) of participants experiencing viral rebound, partial or functional cure. ALT elevation >3X ULN during HBsAg <1 IU/mL and <10 IU/mL were the best predictors of partial and functional cure. In conclusion, elevations in ALT, AST or GGT while HBsAg <10 IU/ml during therapy with REP 2139 + pegIFN are associated with partial and functional cure. More potent HBsAg reduction during flare nadir is associated with the establishment of functional cure, suggesting a critical role for HBsAg‐specific immunity to achieve this outcome. These on‐therapy milestones may have similar positive prognostic value with other combination therapies.